Decentralized controlunified approach and comparison methods - Macháček, Jiří (Univerzita Pardubice, 2006)
Unified approach to methods for decentralized control of the interacting multivariable systems without knowledge of system model is oresented. Common basic of these methods is knowledge of stability limit, which is obtained experimentally by a relay autotuning method. These methods may be interpreted as methods which solve system of nonlinear equations with various numbers of unknown parameters. Control simulations are performed on 2 x 2 and 3 x 3 systems, and some recommendations for practical applications are given on the basic of these simulations.
Keywords: decentralizace; regulátory; řízení; Kontrola; znalostní systémy; srovnávací metody